IT Governance Dengan Penerapan Framework Cobit 5 Pada SMAS GKPI Pamen Medan - Saskia Sitopu, Dinan; Lismardiana Sembiring; Bersama Sinuraya (Universitas Mandiri Bina Prestasi, 2025)
Information technology (IT) has been widely applied to educational institutions or educational organizations. Gkpi Padang Bulan School is a school located on Jl. Lt. Gen. Jamin Ginting Pamen Complex, Padang Bulan, Kec. Medan Baru, Medan City Prov. North Sumatra, which has implemented information technology for several school needs. One of the information technologies used is the school information system. The main activity in the school, namely as an education provider, is to assist in school education information services. In carrying out the main activity, administration is a place for providing administrative services and information about the school. However, there are problems in the current school information system, namely supervision and assessment of IT performance, especially the school information system used and evaluation of system performance has not been carried out optimally by the school because of monitoring and assessment of IT.